Therapeutic activity of lipoxin A4 in TiO2-induced arthritis in mice: NF-κB and Nrf2 in synovial fluid leukocytes and neuronal TRPV1 mechanisms - Saraiva-Santos, Telma; Zaninelli, Tiago H.; Manchope, Marília F.; Andrade, Ketlem C.; Ferraz, Camila R.; Bertozzi, Mariana M.; Artero, Nayara A.; Franciosi, Anelise; Badaro-Garcia, Stephanie; Staurengo-Ferrari, Larissa; Borghi, Sergio M.; Ceravolo, Graziela S.; et al. (Frontiers in Immunology, 2023)
Lipoxin A4 (LXA4) has anti-inflammatory and pro-resolutive roles in inflammation. We evaluated the effects and mechanisms of action of LXA4 in titanium dioxide (TiO2) arthritis, a model of prosthesis-induced joint inflammation and pain. Mice were stimulated with TiO2 (3mg) in the knee joint followed by LXA4 (0.1, 1, or 10ng/animal) or vehicle (ethanol 3.2% in saline) administration. Pain-like behavior and inflammation were measured at several doses to assess the effects of LXA4 in vivo. LXA4 reduced mechanical and thermal hyperalgesia, histopathological damage, edema, and recruitment of leukocytes without liver, kidney, or stomach toxicity. LXA4 reduced leukocyte migration and modulated cytokine production. These effects were explained by reduced nuclear factor kappa B (NF-κB) activation in CD45+F4/80+ macrophages. LXA4 improved antioxidant parameters [reduced glutathione (GSH) and 2,2-azino-bis 3-ethylbenzothiazoline-6-sulfonate (ABTS) levels, nuclear factor erythroid 2-related factor 2 (Nrf2) mRNA and Nrf2 protein expression], reducing reactive oxygen species (ROS) fluorescent detection induced by TiO2 in synovial fluid leukocytes. We observed an increase of lipoxin receptor (ALX/FPR2) in transient receptor potential cation channel subfamily V member 1 (TRPV1)+ DRG nociceptive neurons upon TiO2 inflammation. LXA4 reduced TiO2‐induced TRPV1 mRNA expression and protein detection, as well TRPV1 co-staining with p-NFκB, indicating reduction of neuronal activation. LXA4 down-modulated neuronal activation and response to capsaicin (a TRPV1 agonist) and AITC [a transient receptor potential ankyrin 1 (TRPA1) agonist] of DRG neurons. In conclusion, LXA4 may target recruited leukocytes and primary afferent nociceptive neurons to exert analgesic and anti-inflammatory activities in a mouse model of prosthesis inflammation.